PEMETAAN DAN PENGEMBANGAN WILAYAH POTENSI PARIWISATA DI DESA SELONG BELANAK, KABUPATEN LOMBOK TENGAH - Nurcholisah, Andini; Supriyadi, Didy Ika; Ranggabarani, Amir Zaman Fikhra; Sugiarta, Lalu Ade; Andriani, Suhadah; Saraswati, Gadis Rahayu Harum; Urwatulwutsqo, Baiq Zhalixa Rida; Rahmayati, Nisa Dwi; Haifa, Hasna Nur; Widnur, Rifki Wahyuhadi; Novita, Dien (Universitas Mataram, 2024)
Selong Belanak Village is a village located in the south of Lombok Island. Selong Belanak Beach has its own uniqueness which can become a magnet for visitors, one of which is Selong Belanak Beach. However, it is not only Selong Belanak beach that tourists can visit. Choosing tourist attractions becomes easy if there is a system that provides tourist information in Selong Belanak. Based on the situation analysis regarding the situation in Selong Belanak Village, the UNRAM PMD KKN group designed various activities to answer these problems. The problems that have been identified are grouped into 2 large groups, namely mapping village potential and developing village potential. From the mapping results, there are four categories of tourism in the Selong Belanak village area, one of which is beach tourism. Beach tourism also has six tourist attractions that tourists can visit. There are several accommodation accommodations in Selong Belanak village, ranging from resorts, hotels, villas and homestays. In this case, the Selong Belanak Community Service Team takes part in community empowerment in terms of digital-based tourism promotion. The online promotion that will be carried out will use existing websites and social media platforms.